2008
DOI: 10.1001/archinte.168.12.1325
|View full text |Cite
|
Sign up to set email alerts
|

Prevention, Incidence, and Outcomes of Contrast-Induced Acute Kidney Injury

Abstract: Background: Little is known about whether health care providers (physicians) implement preventive care for contrast-induced acute kidney injury (CIAKI). The objectives of our prospective cohort study were (1) to assess provider use of preventive strategies for CIAKI, (2) to determine the incidence of CIAKI, and (3) to examine the association of CIAKI with adverse outcomes at 30 days, including death, need for dialysis, and hospital admission. Methods: We prospectively identified patients with estimated glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 24 publications
1
73
0
1
Order By: Relevance
“…As part of a larger, prospective, observational study investigating the prevention of CIAKI in patients undergoing coronary or noncoronary angiography or computed tomography at an academically affiliated VA Healthcare System between February 1, 2005 and July 31, 2006, we conducted this substudy of patients who underwent computed tomography (19). We prospectively identified all subjects scheduled to undergo computed tomography with IV iodinated contrast in either the inpatient or outpatient setting and recorded the most recent serum creatinine (Scr) within the 60 d before the procedure.…”
Section: Patient Populationmentioning
confidence: 99%
“…As part of a larger, prospective, observational study investigating the prevention of CIAKI in patients undergoing coronary or noncoronary angiography or computed tomography at an academically affiliated VA Healthcare System between February 1, 2005 and July 31, 2006, we conducted this substudy of patients who underwent computed tomography (19). We prospectively identified all subjects scheduled to undergo computed tomography with IV iodinated contrast in either the inpatient or outpatient setting and recorded the most recent serum creatinine (Scr) within the 60 d before the procedure.…”
Section: Patient Populationmentioning
confidence: 99%
“…There are many strategies available to clinicians to mitigate the risk of contrastinduced nephropathy. However, studies have shown that these techniques (pre-hydration with intravenous fluids and administration of N-acetylcysteine) are inconsistently used in practice [4]. A systematic review and meta-analysis of contrast induced acute kidney injury showed no difference between patients who did and did not receive contrast, regardless of previous renal insufficiency, making the withholding of contrasted imaging unnecessary [5].…”
Section: Discussion and Teachable Momentmentioning
confidence: 99%
“…Practical inclusion criteria for a prevention trial would be CKD based on a GFR of 15-59 ml/min per 1.73 m 2 and the presence of at least one other risk factor such as heart failure, diabetes, or proteinuria among patients with an eGFR of 45-59 ml/min per 1.73 m 2 . Event rates for AKI and AKI requiring dialysis are expected to be 10%-15% and 1.0%, respectively, in patients with CKD (20). For phase 2 studies, an appropriate primary study outcome might be an increase in SCr of $0.5 mg/dl or $25% with multiple SCr assessments over a minimum of 96 hours.…”
Section: Discussionmentioning
confidence: 99%